Assessment of genetic diversity in late flowering almond varieties using ISSR molecular markers aimed to select genotypes tolerant to early spring frost in Yazd province - Reza Ghaffarian, Arman Mahmoudi Otaghvari and Mohammad (Current Botany, 2011)
<span style="font-size: 8pt; layout-grid-mode: line; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The genetic diversity of 19 late flowering almond genotypes in Yazd province were assessed using ISSR markers. 10 selected ISSR primers revealed 101 polymorphic bands among which the 5`-G(AG)7ASG-3` with 17 and 5`-A(GA)7GSC-3` with 3 bands had the most and the least polymorphic bands respectively. In principal component analysis the explanation of a minor part of the total diversity by few prior components as well as the distribution of total variance among different components, indicate the relevant scattering of the ISSR primers through the genome and the validity of ISSR data for the genetic analysis in almond germplasm. The most genetic similarity in cluster analysis was observed between the genotypes 88 and 191. The high genetic similarity between some genotypes may be caused by their common origin or the geographical similarity between their regions of cultivation and improvement. The transfer and translocation of these genotypes among different studied regions have been carried out frequently. The results of molecular analysis showed that almond varieties and genotypes that are collected from close geographical regions all over the Yazd province are of large genetic homogeneity and the overall polymorphism content in studied genomes is rather low. Considering the self-incompatible nature of the almond plants, it may be concluded that the domesticated genotypes and those cultivated in studied regions, have had little mixture with alien almond germplasm